(3dfCcd hfdYH hfJeJY HGdUMI (B/s - (3hhcQ, OHdjh BdGfs; (3gheaQjR, chQJjfj s; (3ecJHI LQjQ (B((3GdQjGV(B)s ((3GdQjGV (B:s (3ecJHI LQjQ,s, 2006)
(3jSGYO GdcJGH aj JTcjd GdYGOGJ GdZPGFjI dOj GdCWaGd efP GdHOGjI(B.s
(3Odjd cdjI GdWH aj LGeYI gGQaGQO ddWYGe GdUMj ddCWaGd (B.s
Keywords: (3GdCWaGds -- (3JZPjIs; (3GdCWaGds -- (3UMI hfXGaIs